Perception of loneliness in older adults in the locality of Molas, Yucatan - Kú, Francelia M. (Consorcio de Universidades Mexicanas A.C., 2017)
The research aimed to explore if the feeling of loneliness is present in older adults in Molas, Yucatan, as well as to know their perception and meaning for it. Aspects such as family, interpersonal relations, culture, feelings, emotions, work situation were considered as possible factors involved in their perception of the feeling of loneliness. We interviewed 25 people for the collection of information. The results obtained show that the feeling of loneliness is not present in the participants due to the culture of the locality and the closeness of their relatives and friends.